2021
DOI: 10.1002/bse.2934
|View full text |Cite
|
Sign up to set email alerts
|

Sustainability risk and portfolio management—A strategic scenario method for sustainable product development

Abstract: Companies need to strategically develop their portfolio and find the balance between being proactive and passive in relation to sustainability. In this study, a strategic perspective based on backcasting from overarching socio-ecological sustainability principles was used as a lens to understand how companies might adapt their product portfolios to avoid threats and exploit opportunities on increasingly sustainabilitydriven markets. The study shows that sustainability performance, market success, and time are … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
15
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3
3
1

Relationship

1
6

Authors

Journals

citations
Cited by 26 publications
(22 citation statements)
references
References 55 publications
1
15
0
Order By: Relevance
“…Sustainable design will be influenced by the megatrends digitalization and circular economy (Brahma, 2021). A similar conclusion is drawn in Hallstedt et al (2021), who concluded that digitalisation, sustainability, and servitisation are intertwined areas, and that circular economy in combination with digitalisation is a key to realize Product Service System solutions and to meet society's challenges and stakeholders' sustainability requirements in terms of resource savings and more efficient usage of products.…”
Section: Introductionsupporting
confidence: 68%
See 2 more Smart Citations
“…Sustainable design will be influenced by the megatrends digitalization and circular economy (Brahma, 2021). A similar conclusion is drawn in Hallstedt et al (2021), who concluded that digitalisation, sustainability, and servitisation are intertwined areas, and that circular economy in combination with digitalisation is a key to realize Product Service System solutions and to meet society's challenges and stakeholders' sustainability requirements in terms of resource savings and more efficient usage of products.…”
Section: Introductionsupporting
confidence: 68%
“…The role of designers is expected to change from design of artefacts to design of entire solutions (see e.g., Isaksson et al, 2009). This implies that designers need to consider the behaviour of products and solutions and their impact over complete life cycles (Ramani et al, 2010;Carlsson et al, 2021), developed and organized by business networks together with several suppliers and other partners with different capabilities (Hallstedt et al 2021).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The review reports a correlation between the maturity of foresight practices within companies and company performances; however, there is no evidence that scenario analysis results in ‘great strategies that are unique, creative, or distant from the industry status quo’ nor direct evidence that scenario analysis improves long‐term business performance (Wiebe et al, 2018). Also in the sustainability domain, scenario analysis has shown its practical relevance to inform company decisions (Villamil et al, 2021) with high relevance to assessing and managing climate‐related risks and opportunities (Hillmann et al, 2018; Linnenluecke & Griffiths, 2012). However, climate change scenario analysis by non‐financial companies is relatively recent with limited best practices (TCFD Status Reports, 2020, 2021).…”
Section: Theoretical Frameworkmentioning
confidence: 99%
“…A large number of different "improvements" were proposed to fulfil the portfolio designers' dreams. Authors in their literature review [2] on sustainability, indicated that a general portfolio setting followed selection criteria and the company's strategies, which are usually based on management elements, e.g., time, cost, risk, quality, etc., leaving the sustainability variables behind. The following are a couple of examples.…”
Section: Introductionmentioning
confidence: 99%